2015 Nutrition subregion profile: Western Asia - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
The subregion profiles capture the status and progress of all countries within the region, and the 80+ indicators include a wealth of information on child, adolescent and adult anthropometry and nutritional status, in addition to intervention coverage, food supply, economics, and demography. This tool is particularly useful for nutrition champions at the country-level, as it presents a wide range of evidence needed to assess country progress in improving nutrition and nutrition-related outcomes.